2023
DOI: 10.1002/advs.202207518
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Osteosarcoma Induced Distant Pre‐Metastatic Niche in Lung to Facilitate the Colonization of Circulating Tumor Cells

Fan Tang,
Yan Tie,
Tian‐Xia Lan
et al.

Abstract: Recently, the major challenge in treating osteosarcoma patients is the metastatic disease, most commonly in the lungs. However, the underlying mechanism of recurrence and metastasis of osteosarcoma after surgical resection of primary tumor remains unclear. This study aims to investigate whether the pulmonary metastases characteristic of osteosarcoma is associated with surgical treatment and whether surgery contributes to the formation of pre‐metastatic niche in the distant lung tissue. In the current study, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…Utilizing a novel combinatorial approach of experimental in vivo platforms (Primary-No Primary, Early amputation, Red-green), we provide evidence to support that primary tumors influence circulating tumor cell fate and impair lung colonization, which agrees with recent findings from other groups[34, 35]. We significantly add to this growing body of literature, finding that in the presence of micro-metastatic disease, circulating tumor cells overwhelmingly favored recruitment to the established micro-metastatic lesions over initiating new ones.…”
Section: Discussionsupporting
confidence: 88%
“…Utilizing a novel combinatorial approach of experimental in vivo platforms (Primary-No Primary, Early amputation, Red-green), we provide evidence to support that primary tumors influence circulating tumor cell fate and impair lung colonization, which agrees with recent findings from other groups[34, 35]. We significantly add to this growing body of literature, finding that in the presence of micro-metastatic disease, circulating tumor cells overwhelmingly favored recruitment to the established micro-metastatic lesions over initiating new ones.…”
Section: Discussionsupporting
confidence: 88%
“…Stages 2 and 3 represent moderate levels. Through the production of growth hormones and cytokines, it has been shown that tumor cells play a pivotal function in guiding cells originating from the bone marrow (Tang et al 2023) toward potential metastatic locations, hence fostering the creation of pre-metastatic niches that support tumor growth. Furthermore, it has become clear that two critical factors controlling pre-metastatic areas are hypoxia induction inside the primary tumor and tumor-derived exosomes.…”
Section: Discussionmentioning
confidence: 99%